2007
DOI: 10.1007/s11270-007-9375-3
|View full text |Cite
|
Sign up to set email alerts
|

Time Course Transformations and Fate of Mercury in Aquatic Model Ecosystems

Abstract: Model aquatic ecosystems have been used to study the natural mechanisms involved in the distribution and transformation of inorganic mercury (IHg) in the different compartments and its interactions with the biota. Laboratory incubations in indoor freshwater microcosms, presenting a simple biological organization, were carried out at various spiked concentrations (3, 25 and 257 nmol l −1 of IHg, as mercuric chloride) and from a single initial contamination of the water column. The different compartments of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…So there were higher levels of total Me 203 Hg in the microcosms without B. caissarum. In an incubation experiment, with sediment, freshwater, waterweeds and snails, Tessier et al (2007) also recorded higher MeHg concentrations in the water column of the control microcosms. The same authors observed a higher content of inorganic Hg in water available for methylation in the control systems when compared to the treatments, suggesting this as a possible reason for the increased MeHg concentration in the controls.…”
Section: Mehg In Seawater and B Caissarummentioning
confidence: 83%
See 4 more Smart Citations
“…So there were higher levels of total Me 203 Hg in the microcosms without B. caissarum. In an incubation experiment, with sediment, freshwater, waterweeds and snails, Tessier et al (2007) also recorded higher MeHg concentrations in the water column of the control microcosms. The same authors observed a higher content of inorganic Hg in water available for methylation in the control systems when compared to the treatments, suggesting this as a possible reason for the increased MeHg concentration in the controls.…”
Section: Mehg In Seawater and B Caissarummentioning
confidence: 83%
“…Several authors have observed the production of MeHg in the water column of freshwater systems (Ribeiro Guevara et al, 2008Guevara et al, , 2007Tessier et al, 2007), although Hg methylation is considered to occur predominantly in sediment , periphyton (Correia et al, 2012b;Mauro et al, 2002) and epilithon (Desrosiers et al, 2006). Koron et al (2012) detected Me 197 Hg production in seawater of incubation experiments with the radiotracer 197 Hg in different incubation periods.…”
Section: Mehg In Seawater and B Caissarummentioning
confidence: 99%
See 3 more Smart Citations